SEGNALAZIONE DI UN LIVELLO FOSSILIFERO DEL TRIAS SUPERIORE IN LOCALITÀ PRA BRUSCHÉ (BELLAGIO, F. 32 I NW) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2023)
A new outcrop with Rhaetavicula contorta was found on the northeast slope of the M. Ponciv, at Pra Brusché (1065 m s.l.m.). The outcrop has the same lithologic characters of the typical « Avicula contorta levels » but its faunal content is quite peculiar. Microfauna and macrofauna were examined in detail and the results compared with the bibliographic data relevant to the « Avicula contorta levels ».
Keywords: Biostratigraphy; Foraminifera; Lamellibranchiata; Upper Triassic; Lombardy (Ita!y).